Pemodelan Simulasi Antena Stretchable Untuk Aplikasi RADAR - Syahputra, Muclas Habib; Rahayu, Yusnita; Wahyu, Yuyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Current technological advances and developments require the academic community to continue to innovate to build the country by improving science and technology. One area of concern for researchers is Electronics and Telecommunications. Part of the science that is currently quite indemand is the antenna. In this study discusses Stretchable Antenna Simulation Modeling for RADAR Applications, the antenna is designed using Polydimethysiloxane (PDMS) material so that theantenna can be bent and adjusted to its placement. The antenna is made with an Ultra Wideband (UWB) frequency in the frequency range of 3.1 – 10.6 Ghz with a minimum bandwidth of > 500 MHz and a return loss of < -10 dB with a VSWR of < 2, so that the antenna can detect according to radar capabilities because this frequency has wide bandwidth. When this antenna is simulated the antenna can work at a center frequency of 3.4 GHz with a bandwidth of > 500 MHz, then when the antenna is bent it does not experience a significant change in frequency, judging from the bandwidth obtained is the same but the return loss is getting lower to -43 dB but still at a frequency of 3.4 GHz.Keywords: Antena, Polydimethylsiloxane (PDMS), AgNw, Stretchable, Bending, RADAR, Ultra Wideband (UWB).